La marche de type machi aruki まち歩きpour prévenir les risques de catastrophes - Takeuchi Yukiko (Projets de Paysage)
Japan is permanently subjected to disasters such as earthquakes, tsunamis, landslides, floods, volcanic eruptions, and typhoons which cause many casualties and a great deal of damage to property each year. Education for risk prevention is an indispensable part of the curriculum of primary and secondary schools. But wouldn't the first challenge for such a curriculum be to include concrete guidelines in the event of a disaster? This article gives an account of an educational approach focused on the experience and careful observation of the everyday environment using geography and the traces of past events in the landscape: the machi aruki まち歩き technique inspired by participative urban planning. The article presents an experiment carried out in the primary school of the district of Uchinomaki in the city of Aso in Kumamoto County which was subjected to violent floods following heavy rainfall in Kyūshū in 2012.